1989
DOI: 10.1128/mcb.9.8.3509
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of heat-resistant mouse tumor cell strains: a new member of the HSP70 family.

Abstract: A series of heat-resistant mutants selected from a murine tumor cell line, RIF-1, display a markedly increased and stable resistance to heat shock. The mutant cell lines were analyzed for differences that may explain their increased resistance. Membrane lipid analysis showed no change in cholesterol content but an increase in the proportion of saturated fatty acids in the phospholipid fraction. Two-dimensional gel analysis revealed a generally increased constitutive synthesis of several major heat shock protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…localization of porphyrin with resulting structural and enzymatic mitochondrial damage after PDT. Recent data suggest that thermal resistance observed in the RIF-TR strains is associated with membrane fluidity alterations (24). Interest ing, we did not observe any significant changes in photosensitivity (comparing the parent RIF-1 and the TR strains) using Photofrin II incubation conditions which would lead to either membrane or mitochondrial damage.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…localization of porphyrin with resulting structural and enzymatic mitochondrial damage after PDT. Recent data suggest that thermal resistance observed in the RIF-TR strains is associated with membrane fluidity alterations (24). Interest ing, we did not observe any significant changes in photosensitivity (comparing the parent RIF-1 and the TR strains) using Photofrin II incubation conditions which would lead to either membrane or mitochondrial damage.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, we have recently observed that porphyrin-mediated PDT can induce a transient increase in mRNA levels of hemeoxygenase and metallothionein.4 Multiple transcription factors can regulate the activation of these genes, and studies focused on PDT-mediated gene regulation may provide information on both target sites and subcellular mechanisms for photosensitizers. Interestingly, heat-resistant cell lines, which have constitutively elevated levels of members of HSP-70 ( 16,24), did not demonstrate cross-resistance to porphyrin-mediated PDT. Therefore, while HSP-70 may modulate thermal sensitivity, it is unlikely that HSP-70 is associated with modification of cellular sensitivity to PDT.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it has been shown that P-internexin, which is a ubiquitous microtubule-and cytoskeleton-associated protein, also corresponds to hsc70 (10). Recently, Anderson et al (1) described a heat-resistant variant of a murine tumor cell line which also contained an electrophoretically altered form of hsc70 (different alteration from that seen in our mutants). However, in contrast to these mutants, our mutants do not show any altered thermotolerance (R. S. Gupta, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…We also exposed cells to the same heat shock but in medium that contained 30 Western blot analysis was then performed to confirm that the 28-kDa protein was HSP28; these results are shown in 2-D gel electrophoresis, but not immunoblotting, shows that HSP70 is coinduced by nicotine and ethanol (or heat). Quantification of proteins by 1-D gels is imprecise; that by 2-D analysis is superior (2). We have therefore repeated all the protein pattern experiments described above with 2-D analysis and quantification of radioactivity of individual spots with an appropriate gel-scanning device (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular proteins were labeled with L-[3H]leucine as described above. The proteins were then subjected to isoelectric focusing in a 3-mm-diameter 3.5% polyacrylamide tube gel followed by electrophoretic separation on a SDS-10% polyacrylamide slab gel (2). Following electrophoresis, the gels were treated as described above for the 1-D gels.…”
Section: Methodsmentioning
confidence: 99%